The law of real property - Megarry, Robert, 1910-2006.; Wade, William, 1918-2004.; Harpum, Charles; Bridge, Stuart; Dixon, Martin (Martin J.) (2012)
This new edition of Megarry & Wade's 'The Law of Real Property' presents a definitive textbook on land law. It provides a comprehensive and up-to-date treatment of land law in England and Wales.
1. Introduction -- 2. Tenures and estates -- 3. Estates -- 4. Possession of land -- 5. Law and equity -- 6. The legislative transformation of the law of real property and the protection of estates and interests -- 7. Registration of title -- 8. Unregistered conveyancing : titles and incumbrances -- 9. Perpetuities and accumulations -- 10. The use of trusts in the law of real property -- 11. Creating trusts of land -- 12. The Trusts of Land and Appointment of Trustees Act 1996 -- 13. Co-ownership -- 14. Wills and intestacy -- 15. Contracts of sale -- 16. Proprietary estoppel -- 17. The nature and creation of leases -- 18. The determination of tenancies -- 19. Common obligations of landlord and tenant -- 20. Leasehold covenants -- 21. Leasehold conveyancing -- 22. Security of tenure -- 23. Fixtures -- 24. The nature and creation of mortgages -- 25. The rights of the parties under a mortgage or charge -- 26. Priority of mortgages -- 27. The nature of easements and profits -- 28. The creation of easements and profits -- 29. Enforcement and extinguishment of easements and profits -- 30. Species of easements and profits -- 31. Other incorporeal hereditaments -- 32. Freehold covenants -- 33. Commonhold -- 34. Licenses -- 35. Adverse possession and limitation -- 36. Disabilities.
At head of cover title: Megarry & Wade.
Includes bibliographical references and index.
Keywords: Real property -- England; Law; Real property; England; England; Wales